Hydroponics: a smart solution for gardening on limited land - Ginting, Maju; Lau, Melia; Hutasoit, Ispandir; Bhakti, Rizki Tri Anugrah (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The hydroponic system is an innovative solution to urban farming challenges, offering an efficient and sustainable method of vegetable cultivation. This system utilizes materials like rockwool, net pots, Rucika pipes, and various plumbing components to create a controlled environment for growing vegetables. The process begins with preparing the planting media and sowing vegetable seeds, followed by setting up the water distribution system and ensuring proper water flow. This system provides numerous benefits, including reducing reliance on traditional farming, promoting food security, and encouraging sustainable agricultural practices. It empowers individuals, particularly housewives and students, to engage in green agriculture, fostering self-reliance and enhancing community welfare. Additionally, the hydroponic system has entrepreneurial potential, opening doors for local businesses focused on fresh vegetable production and the sale of hydroponic systems